Diseño e implementación de un prototipo de controlador de retrolavados automático para estaciones de filtración de agua - Morales-Peña, Luis Alejandro (Instituto Tecnológico de Costa Rica, 2018)
This document shows the design and implementation process of an electronic device intended to control the backwash process of filters in water filtration stations property of Papagayo Servicios Generales PSG Ltda company’s, which is developed according to the requirements and specifications given by the company, as well as the equipment it has. Throughout the text the different stages of design related to the development of the electronic system are shown, in regard to the hardware and software of the device, as well as of the protective casing of it. A functional analysis of the device is also provided, through various logic and electric performance tests. Besides, a comparative analysis between the designed device and the controller used by the company in its maintenance tasks is executed.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018
Keywords: Automatización; Control; Filtros; GUI; ModBus; PCB; PLC; Control; Adquisición; Datos; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics